Ethnomathematical study on the architecture of Seleman Kerinci’s Larik Panjang houses - Asdamayanti, Nurul; Fauzan, Ahmad; Armiati, Armiati; Harisman, Yulyanti (Universitas Islam Negeri Raden Intan Lampung, 2025)
The cultural approach in learning mathematics connects abstract concepts with everyday life, helping students understand mathematics meaningfully. This study aims to explore the ethnomathematics of the Seleman Kerinci’s Larik Panjang house, identifying mathematical contexts in real-world applications. Using an ethnographic approach with qualitative research methods, data collection techniques included observation, documentation, and interviews. The primary data collection instrument was the researcher, supported by observation sheets, interview guidelines, and documentation. The study began with a literature review and geometric material analysis, followed by data reduction, data presentation, verification, and conclusion drawing. The findings reveal mathematical elements in the house’s architecture, including: (1) plane figures such as triangles, rectangles, and rhombuses; (2) solid figures like octagonal prisms and rectangular beams; and (3) transformations involving reflection and rotation. These mathematical aspects demonstrate the integration of indigenous knowledge into architectural design. Ethnomathematics in traditional architecture is expected to serve as an engaging learning medium, making mathematics more relevant to students while preserving local wisdom as part of the nation’s cultural identity. This research contributes to the development of contextual mathematics education, highlighting the importance of cultural heritage in shaping mathematical understanding.